Life cycle assessment of indoor vertical farms - Martin, Michael (Burleigh Dodds Series in Agricultural Science, 2023)
Indoor vertical farms (IVF) have expanded rapidly in recent years as an approach to secure resilient food provisioning in urban areas. Sustainability is often promoted by IVFs, focusing primarily on farm-level metrics and information about work with packaging. However, there are few assessments of the implications IVFs have throughout their life cycle due in part to the novelty of the industry. This chapter aims to provide information and guidance on conducting an environmental sustainability assessment of an IVF employing life cycle assessment (LCA) methodology. Throughout the chapter, the different phases of an LCA are outlined, and guidance is provided for practitioners in order to aid their work, assumptions, and methodological choices. Furthermore, important processes and insights from previous research are provided to promote a more sustainable IVF industry.